ANALISIS TENTANG FAKTOR-FAKTOR KONFLIK SOSIAL ANTARA MASYARAKAT MELAYU DAN MINANGKABAU DI DESA TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Sari, Tika Yurnia; Hambali, Hambali; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: This research is motivated by the existence of a successful team conflict for the selection of village heads, among adolescents, jealousy in formal work, ridicule from the two tribes, holding a wedding, the Minangkabau community living on the watch often not socializing with the local Melayu community in Tarai Bangun Village. The formulation of the problem in this study are the factors that cause the conflict in Tarai Bangun Village and how the conflict occurred in Tarai Bangun Village and what efforts have been made to resolve the conflict in Tarai Bangun Village. The population in this study were the heads of families of Melayu and Minangkabau communities totaling 1,560 households. The number of Melayu tribes is 301 families and the number of Minangkabau tribes is 1,259 families and the sample in this study is 156 families, out of 156 families the authors took 78 Melayu and 78 Minangkabau tribes. Data collection techniques are observation, questionnaire, interview and documentation. Data analysis using quantitative descriptive. The most dominant research results show that the factors that cause conflict in Tarai bangun village are the attitude shown to feel